Formuły subskrypcyjne stosowane w dokumentach arcybiskupa Jarosława Bogorii Skotnickiego oraz personel kancelarii arcybiskupiej w latach 1345-1374 = Subscription formulas used in archbishop Jarosław Bogoria Skotnicki's documents and by the staff of the archbishop's office in years 1354-1374 - Polak, Alina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The workers at archbishop Jarosław Bogoria Skotnicki's office (pontificate from 1342 to 1374) needed suitable education not only to rewrite ready templates but also to edit documents on their own. The staff of the metropolitan office included such clerks as chancellors, vice-chancellors, notaries, pro-notaries and writers.
Keywords: Skotnicki, Jarosław Bogoria (arcybiskup; 1276-1376); Arcybiskupstwo Gnieźnieńskie; 14 w.